Contextualization of Productive Zakat in the Modern Era to Reduce Poverty - Hapsari Wiji Utami (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2023)
This study aims to analyze empirically whether productive zakat has an impact on community economic development. Poverty is a social problem that has not been resolved and continues to emerge along with the times. Thus, the existence of productive zakat in the form of business capital can be a solution as a form of contextualization. To develop the economy, it is necessary to develop the distribution of zakat to micro, small and medium enterprises so that there is cooperation and synergy between individuals. Using a qualitative method by taking primary sources on productive zakat at the zakat institution al-Hidayah Sidoarjo on mustahiq income. The findings show that mustahiq's income is affected by the utilization of productive zakat with a large influence contribution of 41%. This can be seen from the development of income and meeting the needs of mustahiq after participating in the productive zakat empowerment program and the LAZ al-Hidayah Sidoarjo waqf can be used for business capital.